A multilayer network approach to tourism collaboration. (March 2021) - Cehan, Alexandra; Eva, Mihail; Iațu, Corneliu
Abstract : During the last years, tourism studies witnessed an accelerated interest for inquiring stakeholder collaboration by means of Social Network Analysis. However, following a systematic literature review, we identified that little attention has been paid to the different types of relationships that compose a destination's network and especially regarding how these types of relationships interact between themselves. The aim of the current study is to adopt a multilayer network approach in order to decompose stakeholder networks from destinations and analyse the structure of distinct collaboration layers built around different tourism activities, as well as the interdependencies between them. The background of analysis consists of two Romanian case studies, one representative for emerging destinations (Bran) and the other for stagnating ones (Vatra Dornei). Methodologically, Social Network Analysis and nonparametric statistical analysis have been employed in order to uncover general and in-depth aspects of stakeholder collaboration. The main findings point out notable differences in size and structure between the collaboration layers generated by each activity, as well as the fact that particular collaboration layers are significantly interdependent. It has been demonstrated, inter alia, that stakeholders who collaborate for products creation will also collaborate for exchange of knowledge, while those who collaborate for designing policies and strategies will also collaborate for accessing funds and developing common projects. The study has implications for theory building and for destination management, pointing out towards the types of relationships that reinforce each other, and that could maximise collaboration's benefits in destinations, if managed properly.